2006
DOI: 10.1300/j038v12n02_04
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Real Difference Between Conventional and Organic Meat? Investigating Consumers' Attitudes Towards Both Meat Types as an Indicator of Organic Meat's Market Potential

Abstract: The European meat industry is confronted with substantial changes of consumer preferences in relation to the type and quantity of meat in everyday diet. One of the main reasons behind these changes is the public impression that meat is a “dangerous” to consume food. This feeling is the result of recent food scares where meat played a central role and their effect on consumers' perceptions about meat safety. The research at hand explores the market potential of organic meat in Greece and emphasizes the percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 25 publications
5
27
1
Order By: Relevance
“…Ureña et al (2008) reported a WTP of 17.6% for meat and sausages in a Spanish survey study. Krystallis, Arvanitoyannis, and Chryssohoidis (2006) reported that most Greek consumers were willing to pay 85-130% extra for organic chicken. However, consumers in these studies were simply asked how much extra they were willing to pay if the organic meat product would be available.…”
Section: Introductionmentioning
confidence: 99%
“…Ureña et al (2008) reported a WTP of 17.6% for meat and sausages in a Spanish survey study. Krystallis, Arvanitoyannis, and Chryssohoidis (2006) reported that most Greek consumers were willing to pay 85-130% extra for organic chicken. However, consumers in these studies were simply asked how much extra they were willing to pay if the organic meat product would be available.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results are found in survey studies. For example, one study found that 87% of a sample of Greek consumers considers taste to be the most important reason for their meat preferences and another study reports that for 56% of Greek buyers better taste is the main reason for their organic food preference (Krystallis, Arvanitoyannis, & Chryssohoidis, 2006). These studies, together with studies of the cues consumers use to infer the quality of a food product (Becker, 2000;Brunsø, Fjord, & Grunert, 2002), raise the question whether consumers value specific product and process characteristics in their own right or because they use them as cues to eating quality and to form expectations about the pleasure derived from eating the product?…”
Section: Introductionmentioning
confidence: 99%
“…In the few cases in which producers can manage to sell their products as organic, such scarcity of developed channels causes the price differential between organic and conventional products to be still high, feeding a loop characterized by reduced per capita consumption and low presence of organic products in the supermarkets [115][116]. As a consequence, demand and willingness to pay consumers for organic products is reduced [117], especially in relation to beef and in countries such as Spain [118][119], despite being one of the first producers in Europe.…”
Section: Marketing Of Organic Products and Consumer's Behaviormentioning
confidence: 99%
“…In the case of beef, this little demand is partly due to the fact that consumers do not perceive clearly the differences between organic and conventional meat [115]. Therefore, [120] showed that there is a clear need to excel in organic meat products, quality, and environmental contribution.…”
Section: Marketing Of Organic Products and Consumer's Behaviormentioning
confidence: 99%
See 1 more Smart Citation